A review of Solvency II: has it met its objectives? ‐ Abstract of the Edinburgh Discussion. (28th May 2018) - Unknown
Abstract : This abstract relates to the following paper: R.A. Rae, A. Barrett, D. Brooks, M.A. Chotai, A.J. Pelkiewicz and C Wang A review of Solvency II: has it met its objectives? British Actuarial Journal . doi: 10.1017/S1357321717000241